2019
DOI: 10.21203/rs.2.13740/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neonatal sepsis and its associated factors in East Africa: a systematic review and meta-analysis, 2019

Abstract: Background: Neonatal sepsis is one of the most leading causes of inflated death and illness of neonates. Different primary studies in Eastern Africa showed the burden of neonatal sepsis. However, inconsistency among those studies was seen and no review has been conducted to report the amalgamated magnitude and associated factors. Therefore, this review aimed to estimate the national prevalence and associated factors of neonatal sepsis in Eastern Africa. Methods: Using PRISMA guideline, we systematically review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The primary objective of this study was to determine the prevalence and predic- The high prevalence of neonatal sepsis found in this study is expected due to the fact that the study area is a national referral hospital, which receives neonates with severe complications as well as complicated pregnancies. Similar to our findings, a systematic review and meta-analysis conducted in East Africa found a prevalence of neonatal sepsis of 29.7% [25]. The prevalence of neonatal sepsis in the current study is lower than findings from Ethiopia at 45% [5], Tanzanian at [8], Cameroon at 37.9% [6] and Nigeria at 37.6% [7].…”
Section: Discussionsupporting
confidence: 87%
“…The primary objective of this study was to determine the prevalence and predic- The high prevalence of neonatal sepsis found in this study is expected due to the fact that the study area is a national referral hospital, which receives neonates with severe complications as well as complicated pregnancies. Similar to our findings, a systematic review and meta-analysis conducted in East Africa found a prevalence of neonatal sepsis of 29.7% [25]. The prevalence of neonatal sepsis in the current study is lower than findings from Ethiopia at 45% [5], Tanzanian at [8], Cameroon at 37.9% [6] and Nigeria at 37.6% [7].…”
Section: Discussionsupporting
confidence: 87%
“…Table 1 summarizes the characteristics of the 19 included studies in this systematic review and meta-analysis. Twelve studies were from Ethiopia, [32][33][34][35][36][37][38][39][40][41] three from Kenya, one from Rwanda, one from South Sudan, and two from Uganda (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The third and fourth (AW and FG) authors checked the correctness of the data independently. Any disagreements between reviewers were resolved through discussions with third and fourth reviewers when required [37,38]. The mistyping of data was resolved through crosschecking with the included papers.…”
Section: Data Extractionmentioning
confidence: 99%
“…Generally, an increasing number of districts showed incidence rates in the highest category (≥ 47.0/1,000 LB) from 2016 to 2020. The highest number of districts [8] with incidences > 47.0 cases/1,000 LB occurred in 2020, and included three districts (Gulu, Agago, Arua) from Northern Region, three from Western Region (Mbarara, Hoima, Kitagwenda), one from Central Region (Mityana), and one from Eastern Region (Kapchorwa) (Fig. 3).…”
Section: Spatial Distribution Of Neonatal Sepsis Incidence Rates At D...mentioning
confidence: 99%
“…In resource-rich settings with lower neonatal death rates, approximately 9-15% of neonatal deaths are due to sepsis, whereas in resourcelimited settings like Africa with high neonatal death rates, sepsis accounts for 23-27% of neonatal deaths [7]. Risk factors for neonatal sepsis include prematurity, low birth weight (< 2.5 kg), premature rupture of membranes, prolonged labour, caesarean section delivery, maternal infection, and lack of antenatal care [5,[8][9][10]. Home births and lack of skilled birth attendants are also associated with increased risk of neonatal sepsis [11].…”
Section: Introductionmentioning
confidence: 99%